Different Amounts of Nitrogen Fertilizer Applications Alter the Bacterial Diversity and Community Structure in the Rhizosphere Soil of Sugarcane - Gu, Yan; Wang, Jihua; Cai, Weijun; Li, Guoliang; Mei, Yu; Yang, Shaohai (Frontiers in Microbiology, 2021)
Sugarcane cropping systems receive elevated application of nitrogen (N) fertilizer for higher production, which may affect production costs and cause environmental pollution. Therefore, it is critical to elucidate the response of soil microbial to N fertilizer inputs in sugarcane soil. A field experiment was carried out to investigate the effects of optimum (N375, 375 kg N/ha) and excessive (N563, 563 kg N/ha) amounts of N fertilizer on soil bacterial diversity and community structure in a sugarcane cropping system by MiSeq high-throughput sequencing; 50,007 operational taxonomic units (OTUs) were obtained by sequencing the 16S rRNA gene amplicons. Results showed that the most abundant phyla in the sugarcane rhizosphere soil were Proteobacteria, Actinobacteria, Acidobacteria, and Planctomycetes, whose ensemble mean accounted for 74.29%. Different amounts of N application indeed change the bacterial diversity and community structures. Excessive application of N fertilizers significantly decreased the pH and increased the available N in soils and unexpectedly obtained a lower yield. Excessive N resulted in a relatively lower bacterial species richness and significantly increased the relative abundance of phyla Proteobacteria, Acidobacteria, and Bacteroidetes and the genera Sphingomonas and Gemmatimonas, while optimum N treatment significantly increased the phylum Actinobacteria and the genera Bacillus and Nitrospira (P < 0.05). N application shifted the N cycle in nitrification, mainly on the Nitrospira, but showed no significant effect on the genera related to nitrogen fixation, methane oxidation, sulfate reduction, and sulfur oxidation (P > 0.05). Overall, the optimum amount of N application might be conducive to beneficial microorganisms, such as Actinobacteria, Nitrospira, and Bacillus and, thus, result in a healthier ecosystem and higher sustainable crop production.